2022
DOI: 10.3389/fphar.2022.919967
|View full text |Cite
|
Sign up to set email alerts
|

The progress and prospect of natural components in rhubarb (Rheum ribes L.) in the treatment of renal fibrosis

Abstract: Background: Renal fibrosis is a key pathological change that occurs in the progression of almost all chronic kidney diseases . CKD has the characteristics of high morbidity and mortality. Its prevalence is increasing each year on a global scale, which seriously affects people’s health and quality of life. Natural products have been used for new drug development and disease treatment for many years. The abundant natural products in R. ribes L. can intervene in the process of renal fibrosis in different ways and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…This process also exists in the DN. Moreover, through clinical and animal experiments, it is clearly pointed out that [23]: collaterals are highly correlated with the capillary network and the surrounding environment, and it can be considered that the concept of renal fibrosis is related to the collaterals theory of TCM [24][25]. Therefore, we can conduct the treatment of promoting blood circulation and remove the blood stasis according to the theory of kidney complex disease.…”
Section: Discussionmentioning
confidence: 99%
“…This process also exists in the DN. Moreover, through clinical and animal experiments, it is clearly pointed out that [23]: collaterals are highly correlated with the capillary network and the surrounding environment, and it can be considered that the concept of renal fibrosis is related to the collaterals theory of TCM [24][25]. Therefore, we can conduct the treatment of promoting blood circulation and remove the blood stasis according to the theory of kidney complex disease.…”
Section: Discussionmentioning
confidence: 99%
“…The main official parts of Rheum palmatum L. are the root and rhizome. Research has shown that Rheum palmatum L. has several pharmacological properties such as anti-inflammatory, antioxidant, and most importantly, it protects against renal fibrosis ( Wang et al, 2022 ). Rheum palmatum L. can also decrease the abundance of conditionally pathogenic microbes such as Alcaligenaceae, Methanosphaera , and Clostridiaceae in the intestine of 5/6 Nephrectomy rats compared to the CKD model, restoring the functions of the intestinal barrier and alleviating renal fibrosis ( Ji et al, 2020 ).…”
Section: Herbal Medicine Gut-kidney Axis and Dkd/ckdmentioning
confidence: 99%
“…4 From the point of view of modern pharmacology, rhein and emodin are the effective components of Rhubarb, which have been proved to have a protective effect on the kidney. 5 Rhein has the pharmacological effect of anti-tumor and regulating renal function. 6 The pharmacological effects of emodin mainly include anti-cancer, anti-tumor and kidney protection, etc.…”
Section: Introductionmentioning
confidence: 99%